Analysis of Customer Satisfaction Levels with Service Quality at BPR Cempaka Wadah Sejahtera in Teluk Kuantan - Nindia, Nindia; Jushermi, Jushermi; Wildah, Sri Wahyuni (Westscience Press, 2025)
Customer satisfaction is customer feedback on the mismatch between previous expectations and the actual performance they feel after use. This satisfaction is strongly influenced by the quality of service provided by the bank. One important aspect of service quality is assurance, which includes security, trust, and employee competence in providing services to customers. So that quality becomes a major factor for every bank as an indicator of being able to compete with its competitors. This study aims to determine the level of customer satisfaction with service quality and to determine strategies to improve customer satisfaction. The sampling technique was purposive random sampling of 100 respondents of BPR Wadah Cempaka Sejahtera customers. The analysis method used in this research is IPA (Importance Perfomance Analysis) analysis. The results of the Importance Performance Analysis (IPA) analysis of service quality at BPR Cempaka Wadah Sejahtera that in general the services provided have met and even exceeded customer expectations. Therefore, BPR Cempaka Wadah Sejahtera should be able to continue to improve the quality of services provided.